Reproducing and reflecting Latin America and South America: Wendtian and Deweyan analyses of Bolivia, Brazil and Chile in the agent-structure dynamic of the region. - Dijk, Jurre Edsger van (2019)
This dissertation attempts to reveal how state identity leads to the peculiar reproduction of an environment of regional organizations that present themselves as Latin American and South American. The regionalist intercourse in this part of the world is peculiar, because the success of these organizations at producing long-term outputs in material terms is highly dubious. That calls for a more pronouncedly human understanding of regional organizations and the states interacting with and within them: they present characteristics of social groups. The main question asked here, therefore, is: how does state identity affect decisions to create, adhere to, stay in or out of and socially deviate from regional organizations in South America and Latin America? To understand better what identity, state identity and their interactive roles may consist in, this dissertation adopts the ontological premises of conventional social-constructivism to conceptualize them. To then come to a way of measurement, it resorts to the school of pragmatism and employs Deweyan abduction. To study the norms, motives and interests of three Latin American and South American foreign offices and their interaction with their regional environment, discursive data obtained by way of semi-structured interviews with four Brasilia-based diplomats are used. It is concluded that such discourse does not yield a lens onto the mutual reproduction of agents and structure. It rather only presents the regional environment as a reflection of motivations and interests rooted ultimately in the geographic environments of the individual states, which interviewees defined differently for each one. Decisions with respect to the regionalist environment in this part of the world are therefore most often subject to national government actors\' political will, or lack of it. Regionally, such actors\' interests mostly converge when it comes to the mutual defense of national sovereignty. Tentative evidence for a more continuous commonly identified interest beyond that is found for states that define their foreign policies as pragmatic (Brazil, Chile). Such pragmatism being at odds with common institutional structures for a common interest, however, that interest is also still ultimately what national politics makes of it.